Straightjackets of Male Domination in Senior Positions: Revisiting Acker's 'Ideal Worker' and the Construction of the 'Ideal Executive'. (16th November 2020) - Poorhosseinzadeh, Mahan; Strachan, Glenda
Abstract: This paper contributes to the on‐going debate on men's overrepresentation in executive positions. Drawing on semi‐structured interviews with male senior managers in two Australian organizations, this paper aims to problematize men's privilege in senior positions by uncovering the different forms of hegemonic masculinity that legitimize men as the ideal candidates for executive positions. Using Joan Acker's concept of the 'ideal worker' as a starting point, this paper aggregates these criteria to develop a new concept of the 'ideal executive'. The model of the 'ideal executive' reveals how decision‐makers (mostly male) control executive position allocation, construct the barriers to entry and define the criteria for an ideal candidate for such a position. Candidates who desire to be considered for an executive position need to conform to this 'ideal', which has been influenced and shaped by male executives. Patriarchal power structures, particularly careerism and entrepreneurialism, are investigated with a focus on the ways in which they contribute to the construction of the ideal executive and consequently inhibit women's career progression into senior positions. We conclude that masculinities are now more sophisticated and encompass newer forms that account for changes in societal norms.